The Existence Of Islamic Legal Values In The Indonesian Legal System And Their Application In National Legal Development - Muhammad Ali; La Ode Husen; Sahban Sahban (JURNAL HUKUM SEHASEN, 2024)
This research aims to determine and analyze the values of Islamic law in the national legal system and to analyze Islamic legal factors that influence national legal development. This research uses a type of normative legal research that is prospective in nature and focuses on observing legal history and observing/synchronizing law vertically and horizontally. With the technique of collecting secondary legal materials in the form of the existence of Islamic values in the national legal system, then qualitative analysis is carried out descriptively and perspectively. The research results show that (1). Islamic legal values cannot be separated from the character of the national legal system. Islamic legal values also guarantee human rights in their conception in line with the ideals carried out in the formation of the legal system in Indonesia based on the 1945 Constitution. (2). Factors of theological beliefs, historical arguments, and majority aspects are tendencies in efforts to incorporate Islamic legal values in national legal development.